Individualized Diabetic Care is Key for Athletic Success - Parry, Nicola (MD Conference Express, 2013)
There are many challenges when caring for athletes with type 1 diabetes. Since athletic training and competition can markedly disturb blood glucose control, it can be difficult to manage diabetes in individuals who exercise excessively. This article highlights the importance of personalized care to optimize glycemic control for maximal health benefits and athletic success.